Privacy Model For Transaction Management In Mobile Databases - Byamba, Byambasuren (2010)
Data transaction over distributed network has gained much attention in the database communities since the last two decades, especially in terms of security and privacy support. The transactions over wireless network are easy to compromise and available to disclosure, lose and destruction when lack of security and privacy is found in the system. Our research focuses on the privacy of mobile transaction over the wireless network of the MCTO.